HUBUNGAN ANTARA FLAT FOOT DAN KESEIMBANGAN STATIS PADA ANAK SEKOLAH DASAR - Ayu Sundari, (2023)
Background: The feet during the growth and development of children are affected by the shape of the arches of the feet. If a child has a flat foot, it can cause injury. Children with flat feet will feel uncomfortable due to abnormal walking patterns and will tire easily, which can cause balance disturbances. Purpose: This study aims to determine the relationship between flat feet and static body balance in elementary school children. Method: The research method used is correlational quantitative with a cross sectional approach. As many as 98 students of Limo 01 State Elementary School participated in this study, the parameters used were the Wet Footprint Test and Clarke's Angle to determine the degree of foot arch and the Stork Standing Test to measure static balance. Results: The results obtained were for the Wet Footprint Test and Clarke's Angle in the Flat foot category with a percentage of 100%, for the Stork Standing Test in the average category with a percentage of 43.9% with a sig. (2-tailed) namely p = 0.000 with p < 0.05. Conclusion: the conclusion of this study is that there is a significant relationship between flat feet and body static balance.